Enhancing Accountability of Government-Linked Companies through Supply Chain Management Practices - Kasim, Eley Suzana; Omar, Normah; Said, Jamaliah; Abdul Rahman, Ibrahim Kamal (International Journal of Supply Chain Management, 2019)
Accountability has long been the major focus of government-linked companies (GLCs) as these firms are directly accountable to the taxpayers. While studies examining accountability of GLCs are widely available, very little evidence exist in investigating how these GLCs achieve accountability through supply chain management (SCM). Thus, the aim of the present research is to gain insights into how SCM practices create value to the firm, which in turn enhance accountability of the GLCs towards its ultimate stakeholders. A single case study approach was used whereby key research issues were mainly addressed through semi-structured interviews, observations and document reviews. Findings revealed that, consistent with the financial and social obligations of the GLC to its stakeholders, the firm was able to create value through supplier involvement, strategic supplier relationship and supplier development practices. The findings provide valuable input for similar companies to emulate these practices in order to achieve accountability through SCM practices.